P300-dependent STAT3 acetylation is necessary for angiotensin II-induced pro-fibrotic responses in renal tubular epithelial cells - Ni, Jun; Shen, Yang; Wang, Zhen; Shao, De-cui; Liu, Jia; Kong, Ya-li; Fu, Lan-jun; Zhou, Li; Xue, Hong; Huang, Yu; Zhang, Wei; Yu, Chen; et al. (Acta pharmacologica Sinica, 2014)
Aim： To explore the role of signal transducer and activator of transcription 3 （STAT3） signaling pathway, especially STAT3 acetylation, in angiotensin II （Ang II）-induced pro-fibrotic responses in renal tubular epithelial cells. Methods： Rat renal tubular epithelial cell line （NRK-52E） was used. STAT3 acetylation, phosphorylation and Janus kinase 2 （Jak2） phosphorylation, as well as the expression of fibronectin, collagen IV, transforming growth factor-131 （TGF-β1） and p300 were examined using Western blotting. The level and localization of STAT3 phosphorylation on Tyr705 were detected with fluorescence immunocytochemistry. The cells were transfected with a plasmid vector carrying p300 gene or siRNA targeting p300 to regulate p300 expression. Results： Overexpression of p300 significantly increased STAT3 acetylation on Lys685, STAT3 phosphorylation on Tyr705, and the expression of TGF-β1, collagen IV and fibronectin in the cells. Treatment of the cells with Ang II （1 pmol/L） significantly increased STAT3 phosphorylation on Tyr705 through JAK2 activation, and dose-dependently increased the expression of fibronectin, collagen IV and TGF-β1. Pretreatment with curcumin, an inhibitor of JAK2 and p300, blocked Ang II-induced effects. Knockdown of p300 significantly decreased STAT3 acetylation on Lys685, and abolished Ang II-stimulated STAT3 phosphorylation on Tyr705, whereas pretreatment of the cells with C646, a selective inhibitor of p300, inhibited Ang II-induced STAT3 nuclear translocation and the expression of TGF- 131, collagen IV and fibronectin. Pretreatment of the cells with AG490, a JAK2 inhibitor, markedly inhibited Ang II-induced STAT3 phosphorylation on Tyr705 and fibronectin expression. Conclusion： P300-dependent STAT3 acetylation is necessary for Ang II-induced STAT3 phosphorylation and the consequent pro-fibrotic responses in renal tubular epithelial cells in vitro.